Antibiotic Prophylaxis in Elective Hand Surgery - Vasconcelos, Carolina; Serra, Marta; Nogueira, Rúben; Carmo, Leonor do (Revista Iberoamericana de Cirugía de la Mano, 2017)
Purpose Antibiotic prophylaxis decreases the rate of surgical site infection in a broad spectrum of surgical procedures. However, in patients undergoing elective hand surgery, there is evidence of lower efficacy, and its use might be related to the development of antimicrobial resistance. The side effects and higher health-related costs must also be taken into consideration. Our aim was to assess the efficacy of antibiotic prophylaxis in these procedures.Material and methods A retrospective study was conducted including all patients who underwent clean, elective hand surgery lasting less than 30 minutes from January 1st 2014 to December 31st 2015 at our hospital. The demographic and surgery-related data were analyzed using the Statistical Package for the Social Sciences (SPSS, IBM Corp., Armonk, NY, US) software, version 23.0.Results A total of 346 patients matched the study's inclusion criteria. The infection rate was of 1%, and it was not influenced by gender, age or diabetes mellitus. Antibiotic prophylaxis was administered in 52% of the cases, and it had no effect on the decrease in the infection rate, even in the group of diabetic patients.Conclusions Despite the inherent limitations of any retrospective study, our data analysis supports the fact that prophylactic antibiotic administration does not reduce the incidence of surgical site infection in clean, elective hand surgery that lasts less than 30 minutes, even in patients at risk.
Keywords: hand surgery; antibiotic prophylaxis; infection